2014
DOI: 10.1159/000363214
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Risk of Falling after Cochlear Implantation

Abstract: Cochlear implantation is a highly effective intervention for hearing loss, but insertion of an implant into the cochlea is often accompanied by loss of residual hearing function. Sometimes, postoperative testing also shows loss of function in the semicircular canals or otolith organs. The effect of this loss on equilibrium, particularly in the short term following surgery, and the risk of falling due to this loss is unknown. We prospectively measured balance in 16 consecutive adult cochlear implant patients be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Despite quantitative improvements in balance, none of our participants reported a subjective improvement when wearing their hearing aids either before or after our testing session. This is consistent with previous work showing a poor correlation between subjective and objective measures of balance and postural stability . This finding may be particularly important because it suggests that identifying patients whose balance might improve with hearing aids should not rely on the patient's own estimate of the effectiveness of amplification on balance.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Despite quantitative improvements in balance, none of our participants reported a subjective improvement when wearing their hearing aids either before or after our testing session. This is consistent with previous work showing a poor correlation between subjective and objective measures of balance and postural stability . This finding may be particularly important because it suggests that identifying patients whose balance might improve with hearing aids should not rely on the patient's own estimate of the effectiveness of amplification on balance.…”
Section: Discussionsupporting
confidence: 90%
“…A published abstract consisting of a case study of a patient with single‐sided deafness reported that postural sway was reduced when the implant was turned on . Although these studies are suggestive of a benefit due to cochlear implantation, it is important to recognize that balance may actually worsen, at least temporarily, presumably from labyrinthine trauma during to the surgical implantation procedure itself …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common symptoms are vertigo, dizziness, and imbalance [10]. The risk of falls has been found to increase in 56% of all cochlear implantees (and 40% of implantees who had normal balance prior to implantation); older implantees have also been found to exhibit worse balance than younger implantees [1113]. Most of these complications are episodic, and some are transient [14], but researchers also point to delayed effects and possible histopathologic damage that may not present symptoms [13, 1517].…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative side effects of vertigo and imbalance occur in 34% of all CI patients 5. Stevens et al reported that the risk of falls increases postoperatively in 40% of patients who had normal balance prior to the CI and in 56% of all patients 6. Thus, these particular patients need to choose between improved hearing or balance.…”
Section: Introductionmentioning
confidence: 99%